PENYULUHAN DEMAM BERDARAH DAN RESISTENSI INSEKTISIDA ANTINYAMUK DI DESA OEBELO, KABUPATEN KUPANG, NUSA TENGGARA TIMUR - Jemris Sabneno; Alexsandra Pallo Sungga; Natasha Imanuelle Yeri; Oriza Surya Ningsih; Agatha Sada Ua; Christina Debby De Jesus; Brito Ara Ujo; Diana Agustiani Wuri; Novalino Harold Geoffrey Kallau; Annytha Ina Rohi Detha; Larry Richard Wellem Toha; Delfina Gregoriana Gusmaõ Alves (Universitas Nusa Cendana, 2022)
Dengue Hemorrhagic Fever in the east nusa tenggara currently dominates the third highest number in Indonesia. This outreach activity was carried out in Oebelo Village, Kupang Regency, East Nusa Tenggara Province on Dengue Hemorrhagic Fever and Anti-Mosquito Insecticide Resistance. The method used The method used in this extension is the lecture and discussion method. The purpose of this outreach is to provide information to the public about Dengue Hemorrhagic Fever and its control and control efforts with 4M. The conclusions obtained are increased understanding of the eradication of mosquito nests 4M plus, increased public understanding of the bioecological vectors that cause dengue fever, increased understanding of mosquito repellent insecticide resistance and possible uses as mosquito repellent insecticides.